2016
DOI: 10.1161/circep.115.003874
|View full text |Cite
|
Sign up to set email alerts
|

Results of Cryoenergy and Radiofrequency-Based Catheter Ablation for Treating Ventricular Arrhythmias Arising From the Papillary Muscles of the Left Ventricle, Guided by Intracardiac Echocardiography and Image Integration

Abstract: T he papillary muscles (PMs) from the left ventricle (LV) have been shown to be a potential site of origin of ventricular arrhythmias (VAs) in patients with and without structural heart disease.1 Catheter ablation has been described as an effective treatment for these arrhythmias, although radiofrequency delivery at these regions has been associated with poor manipulation and catheter stability compared with other VAs. 2 See Editorial by Latchamsetty and BogunPrevious data on catheter cryoablation of PMs VAs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 29 publications
1
60
1
1
Order By: Relevance
“…Yamada et al 3 reported that there was no evidence of significant MR after RF CA of PMs in 19 patients during a median follow-up period of 21 months (APM, n = 7; PPM, n = 12). Similarly, Rivera et al 5 reported that there was no increase in the incidence of MR or an increase in MR severity in 21 patients, including 5 patients with MVP, after CA of PMs using either cryoenergy (n = 12) or RF energy (n = 9). However, a case of bileaflet MVP and VT who developed severe MR after CA targeting PM-derived VA was reported by DeSimone et al 6 In the present case, MR worsened during an 8-month follow-up period.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Yamada et al 3 reported that there was no evidence of significant MR after RF CA of PMs in 19 patients during a median follow-up period of 21 months (APM, n = 7; PPM, n = 12). Similarly, Rivera et al 5 reported that there was no increase in the incidence of MR or an increase in MR severity in 21 patients, including 5 patients with MVP, after CA of PMs using either cryoenergy (n = 12) or RF energy (n = 9). However, a case of bileaflet MVP and VT who developed severe MR after CA targeting PM-derived VA was reported by DeSimone et al 6 In the present case, MR worsened during an 8-month follow-up period.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, a “malignant” arrhythmia phenotype in patients with mitral valve prolapse (MVP) who experienced life-threatening VAs has been reported. This subset of patients with MVP was characterized by complex ventricular ectopy arising from one or both of the PMs, fascicular tissue, and outflow tracts,1, 2 and the arrhythmias have been shown to be successfully treated by catheter ablation (CA) 3, 4, 5. Mitral valve dysfunction after radiofrequency (RF) CA of VAs of PM origin has been described in only 1 report, 6 to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…With success defined as a ≥ 50% reduction in VAs, at a mean follow-up of 360 days, the cryoablation group had a 100% success rate versus a 56% success rate at 87 days followup in the RF group. 29 Cryoablation was also associated with a decrease in multiple VA morphologies observed during ablation (0% versus 77%).…”
Section: Early Potentialsmentioning
confidence: 95%
“…18,24 With expanded use of cryoablation, circumferential ablation, and automatic pacemapping, current generation success rates are quoted to be as high as 90% to 100%. 27,29,31 These advances have rapidly transitioned ablation of papillary VA from one of the least successful ablation procedures to one of high probability of cure. The lessons learned from papillary muscle arrhythmia are being applied to other endocavitary structures and may help to improve procedural success rates elsewhere in the future.…”
Section: Our Method/summarymentioning
confidence: 99%
“…Furthermore, a reduction of the PVC burden of <50% of the original PVC burden was used to define success in the study by Rivera et al, 3 whereas the standard definition of successful PVC ablation is a reduction of ≥80%.…”
Section: See Article By Rivera Et Almentioning
confidence: 99%